Diseminasi Alat Pemisah Pupuk Bioslurry dan Diseminasi Pengomposan Pupuk Bioslurry Padat-Kulit Kopi Sebagai Upaya Pengoptimalan Pengelolaan Kotoran Sapi Menjadi Biogas - Sri Ismiyati Damayanti; Nawansih, Otik; Iryani, Dewi Agustina; Ginting, Simparmin Br (FT Universitas Lampung, 2022)
Abstract: The dissemination of the bioslurry fertilizer separator and the dissemination of coffee husk-solid bioslurry fertilizer composting aims to introduce about the bioslurry fertilizer separator into solid and liquid phases, and introduce composting of solid bioslurry fertilizer with coffee husks which is proven to produce compost according to SNI. The specific target of this activity is that the community knows, understands, and has the skills to apply the introduced science and technology so that later they will be able to meet the organic fertilizer needs of their land. The methods used are: (1) Dissemination of the activity plan, (2) Providing materials related to science and technology that will be disseminated, (3). Training on the manufacture of solid-liquid bioslurry fertilizer separator and operation of the equipment, (4). Training on making compost from bioslurry solid fertilizer with coffee husks, (5). Evaluation of community activities. The target of this activity is the village community in general, community groups that have biogas digesters, and the Women Farmers Group (KWT). The location of the activity is in Kediri Village, Gadingrejo District, Pringsewu, Lampung. All activities have been carried out according to the method. Village communities as partners contribute in terms of manpower and consumption during the activity. There are almost no significant obstacles in the implementation of this activity. The outputs are a bioslurry fertilizer separator, a 500 liter capacity fertilizer mixer with a 7.5 pk diesel engine, a journal article, a patent article, and an activity videos that can be accessed on Youtube. Keywords: Bioslurry; Bioslurry Fertilizer Separator; Compost; Coffee Husks; Biogas